Plants and animals as indicators of anthropogenous influence on natural Volga delta ecosystems - T. V. Dymova; V. V. Fedorovich (Юг России: экология, развитие)
The vegetative cover and rich fauna of the Volga delta feel the considerable anthropogenous loadings causing negative changes of specific structure of plants and animals, structure and efficiency of natural ecosystems. The ecological condition of natural Volga delta ecosystems has been defined by means of presence, condition and behaviour of some indicator kinds.